Analisis Pengaruh Jumlah Penduduk, Tingkat Pengangguran Terbuka Dan Indeks Pembangunan Manusia Terhadap Tingkat Kemiskinan Di Provinsi Jawa Timur - Ema Dian Ristika; Wiwin Priana Primandhana; Mohammad Wahed (Universitas Batanghari Jambi, 2021)
Poverty becomes a serious problem because it relates to the welfare of human life. Therefore, there needs to be further assessment of the factors that affect poverty. This study aims to determine the influence of Population, Open Unemployment Rate, and Human Development Index (HDI) on Poverty Level in East Java Province in 2009-2019. This research is quantitative research using secondary data obtained through the website of the Central Statistics Agency of East Java Province. The research method used is Multiple Linear Regression with Ordinary Least Square (OLS) model. The results of this study prove that variable population has a significant effect on the poverty rate of East Java Province, the variable open unemployment rate has no significant effect on the poverty rate of The East Java Province, the human development index variable has a significant effect on the poverty rate of the East Java Province. Simultaneously, the Population, Open Unemployment Rate, and Human Development Index significantly affect the Poverty Rate of East Java Province.